2016
DOI: 10.1177/0956797616638650
|View full text |Cite
|
Sign up to set email alerts
|

Capturing the Interpersonal Implications of Evolved Preferences? Frequency of Sex Shapes Automatic, but Not Explicit, Partner Evaluations

Abstract: Sex is crucial to reproduction, and thus humans likely evolved a strong predisposition to engage in sexual intercourse. Given that meeting interpersonal preferences tends to promote positive relationship evaluations, sex within a relationship should be positively associated with relationship satisfaction. Nevertheless, prior research has been inconclusive in demonstrating such a link, with longitudinal and experimental studies showing no association between sexual frequency and relationship satisfaction. Cruci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 42 publications
3
60
0
Order By: Relevance
“…Studies with the Oxtr variant have shown that individuals with a greater number of G (vs. A) alleles display greater empathy, altruism, sensitive parenting, and sociality (Acevedo, Poulin & Brown, ; Buffone & Poulin, ; Li et al, ; Poulin et al, ; Rodrigues et al, ; Uzefovsky, et al, ). Collectively, these results lend support to models proposing that sustained sexual satisfaction within pair‐bonds, beyond reproduction, may have partly evolved for relationship‐maintenance purposes (Hicks et al, ; Peterson et al, ). This seems like an efficient evolutionary adaptation, as the pair‐bond serves multiple functions from companionship and emotional intimacy, social support, care‐giving, sex, and romantic love (Acevedo et al, ; Collins & Feeney, ).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Studies with the Oxtr variant have shown that individuals with a greater number of G (vs. A) alleles display greater empathy, altruism, sensitive parenting, and sociality (Acevedo, Poulin & Brown, ; Buffone & Poulin, ; Li et al, ; Poulin et al, ; Rodrigues et al, ; Uzefovsky, et al, ). Collectively, these results lend support to models proposing that sustained sexual satisfaction within pair‐bonds, beyond reproduction, may have partly evolved for relationship‐maintenance purposes (Hicks et al, ; Peterson et al, ). This seems like an efficient evolutionary adaptation, as the pair‐bond serves multiple functions from companionship and emotional intimacy, social support, care‐giving, sex, and romantic love (Acevedo et al, ; Collins & Feeney, ).…”
Section: Discussionsupporting
confidence: 80%
“…Finally, research suggests that sex's health benefits may be mediated by releases in dopamine and oxytocin (Meston & Frohlich, 2000). Thus, it is important to investigate both implicit and explicit psychological and physiological measures of sex behaviors (Hicks, McNulty, Meltzer, & Olson, 2016).…”
mentioning
confidence: 99%
“…Already since 1978, Paxton and Turner [53, p.66] explained that -certain types of sexual attitudes and behaviors may be characteristic of self-actualizing females.‖ Thus, in line with the predictions and the results of previous studies [52], self-actualization does not stand independent and become the ultimate relationship goal especially in the romantic one. Rather, on the contrary, through regression analysis (with sexual satisfaction as the dependent variable), selfactualization is found to be devoted to sexual activity [53], which has been robustly proved pivotal as a contributor to relationship satisfaction [54,55]. Furthermore, religious beliefs, goals are found as Factor 3 of Relationship Goals.…”
Section: Discussionmentioning
confidence: 88%
“…Several researchers have expressed their concern regarding the amount and type of sexual portrayals in television content (e.g., Garcia et al, 2012 ; Heldman & Wade, 2010 ). Notwithstanding, sexual intercourse within a committed relationship is generally perceived as a normative and even desired behavior (Hicks, McNulty, Meltzer, & Olson, 2016 ), indicating that such concerns are relatively superfluous as long as sexual behaviors occur within a committed relationship. The results of this content analysis suggest that casual sexual experiences and relationships are almost as frequently shown in popular television programs as sexual behaviors within more traditional committed relationships.…”
Section: Discussionmentioning
confidence: 99%